Evaluation of the KONI Sports Coaching Program in Karangasem Bali Regency - I Putu Darmayasa; Suratmin; Made Juliani; I Putu Panca Adi; Ratna Kumala Setyaningrum; Hanik Liskustyawati (Universitas Pendidikan Ganesha, 2022)
Sports coaching in the Province of Bali are unevenly distributed. It is proven that Karangasem Regency often ranks at the bottom. The fundamental cause experienced by KONI is that the sports coaching program that has yet to be implemented optimally refers to the progress of sports science and technology with scientific studies. The study aimed to evaluate the KONI sports coaching program in Karangasem Regency, Bali Province, using the context, input, process, and product (CIPP) model. Evaluation research uses a combination approach (quantitative and qualitative). The methods used in collecting data are observation, interviews, and documentation. The instrument used in collecting data is a questionnaire sheet. The data analysis used is data triangulation. The results of the study, namely First, recommend the results of the evaluation of the KONI sports coaching program in Karangasem Regency. Second, the KONI policy in Karangasem Regency in the development of sports coaching. Third, realizing sports coaching systems/coaching models at KONI Karangasem Regency. Fourth, make management of sports coaching at KONI Karangasem Regency. Related parties are expected to be able to make a real contribution in the management and development of KONI sports in Karangasem Regency, Bali Province.